2017
DOI: 10.1039/c7cc00557a
|View full text |Cite
|
Sign up to set email alerts
|

A triptycene-based porous hydrogen-bonded organic framework for guest incorporation with tailored fitting

Abstract: A hydrogen-bonded organic framework (HOF) was constructed by avoiding potential π-π stacking of building blocks with robust and non-coplanar triptycene-based modules. The tailored-fitting interactions were demonstrated by the adsorption of fullerene with a concentration enrichment of ∼420 times in the pores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 49 publications
0
69
0
Order By: Relevance
“…Miljanić and co-workers reported as eries of honeycomb HOFs with SA (BET) values ranging from 903 m 2 g À1 to 1821 m 2 g À1 built from tripyrazole derivatives 27-29. [51] These highly porous structures were prepared through asophisticated combination of triangular cyclic H-bonding of three pyrazole moieties and strong p-p stacking between the electron-poor tetrafluorobenzene and relatively electron-rich pyrazole moieties.P ores covered by fluorine atoms are suitable for absorption of fluorocarbons.T ecton 30 produced aframework with 1D pores capable of accommodating C 60 . [52] H-Bonding between pyridiyl groups and Hatoms in amino or amide groups also was applied as supramolecular synthons to construct HOFs with permanent porosity.T ectons 31 [53] and 32 [54] form honeycomb type porous layers.A lthough permanent porosity of the former was not described, the latter (HOF-8)was reported to be thermally stable up to 240 8 8Cand underwent selective sorption of CO 2 and benzene at ambient temperature and pressure. [54] Champness,S chrçder,a nd coworkers demonstrated that tecton 33 formed ap orous 3D networked HOF (SOF-1)with an SA (BET) value of 474 m 2 g À1 and thermal stability up to 420 8 8C.…”
Section: Heterocyclesmentioning
confidence: 99%
“…Miljanić and co-workers reported as eries of honeycomb HOFs with SA (BET) values ranging from 903 m 2 g À1 to 1821 m 2 g À1 built from tripyrazole derivatives 27-29. [51] These highly porous structures were prepared through asophisticated combination of triangular cyclic H-bonding of three pyrazole moieties and strong p-p stacking between the electron-poor tetrafluorobenzene and relatively electron-rich pyrazole moieties.P ores covered by fluorine atoms are suitable for absorption of fluorocarbons.T ecton 30 produced aframework with 1D pores capable of accommodating C 60 . [52] H-Bonding between pyridiyl groups and Hatoms in amino or amide groups also was applied as supramolecular synthons to construct HOFs with permanent porosity.T ectons 31 [53] and 32 [54] form honeycomb type porous layers.A lthough permanent porosity of the former was not described, the latter (HOF-8)was reported to be thermally stable up to 240 8 8Cand underwent selective sorption of CO 2 and benzene at ambient temperature and pressure. [54] Champness,S chrçder,a nd coworkers demonstrated that tecton 33 formed ap orous 3D networked HOF (SOF-1)with an SA (BET) value of 474 m 2 g À1 and thermal stability up to 420 8 8C.…”
Section: Heterocyclesmentioning
confidence: 99%
“…As a result, each pore has equipped with four bared carboxyl oxygen atoms from the two diagonals, which was expected to play the dominate role on the affinities of TCPP‐1,3–DPP . In addition, the two pyridine moieties of 1,3‐DPP were distorted to co‐planar with their respective carboxyphenyl moieties (Figure S2, Supporting Information), resulting the maximal exposure of the molecular surface to the pores, which will contribute significant to the higher porosity of HOF TCPP‐1,3–DPP . In the crystal, the adjacent 1D stripes were further stacked aslant through weak π…π stacking interactions (Table S2, Supporting Information) between one side of a stripe and the other side of the adjacent stripe (Figure e), resulting a 3D porous framework (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, despite these attractive merits, only a handful of robust HOFs with high stability and high permanent porosity have been reported. The majority of them were one‐component crystalline materials with C 3 ‐symmetric skeletons of 2,4‐diaminotriazine group, pyrazole, imidazole, and imidazolone . One thing should be stressed is that most of these reported HOFs were somewhat interpenetrated or packed by strong π···π interactions.…”
Section: Introductionmentioning
confidence: 99%
“…10,[13][14][15][16][17][18][19] However, the stability of SOFs is still a challenge although a number of SOFs with permanent porosity have been reported. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Considering their highly predictable hydrogenbonding motif, some (carboxylic acid)-containing organic units were selected to construct SOF materials by the groups of Zentner, Moorthy, Hisaki and others. 24,[36][37][38][39][40][41] The vast majority of these SOFs are 2D materials due to the limited propagation ability of planar blocks.…”
Section: Introductionmentioning
confidence: 99%